OHVIRA syndrome: a rare variant of mullerian duct anomaly - Rudra, Samar; Dahiya, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
OHVIRA is a rare variety of congenital anomaly of mullerian duct. The syndrome includes uterus didelphys, obstructed hemivagina and ipsilateral renal anomaly, also known as Herlyn-Werner-Wunderlich (HWW) syndrome. A 15yrs old girl was referred to our department with regular menstrual period and cyclic pain in lower abdomen of 5-6 months duration. USG and MRI established the final diagnosis of OHVIRA syndrome. Drainage of hematocolpos of obstructed hemivagina and excision of septum was done and patient was discharged under satisfactory condition to come for follow-up. Patient had her normal menses on 28/8/2015. A repeat USG was done which showed didelphus uterus with no collection in endometrial cavity.